Document management in the Brazilian Public Heath Administration: an analysis from the perspective of Primary Health Care managers - Pinheiro dos Santos, Beatriz Rosa [UNESP]; Martins Damian, Ieda Pelogia (Ibersid Network, 2020)
The document management processes and their presence in the work practices of the managers of family health units in Brazil are analysed. A research of qualitative nature was developed, characterized as descriptive and exploratory, being used as instruments for data collection interviews and systematic observation. To analyze the data, we opted for the Content Analysis method. The results showed that managers could not clearly express what they understood by document management, nor did they efficiently work on the classification, ordering, installation, filing, elimination and preservation of physical records and other documents belonging to the organizational environment. It is stated that the application of the guidelines established in the study contributes to the valorization of the physical records and to the optimization of the documents in the units, as well as to help managers and other professionals in effective decision making, which contributes strongly to the improvement of care and public health services provided to society.
Keywords: Document management; Public Health Administration; Family Health Unit; Primary Health Care; Records management